Mineral transition of high-temperature sintering confirmed in CaAl2O4-Ca2SiO4 non-equilibrium binary system. (20th February 2020) - Zhang, Di; Hu, Sisi; Sun, Huilan; Zhang, Wei; Wang, Bo
Abstract: The mineral transition mechanism, microstructure evolution and chemical reactivity of CaAl2 O4 -Ca2 SiO4 samples during the high-temperature sintering process at 1300–1500 °C were systematically studied using the pre-synthesized CaAl2 O4 and Ca2 SiO4 as raw materials when the mass ratio of Al2 O3 to SiO2 is 3.0. The results show that increasing calcination temperature from 1300–1500 °C could promote the process CaAl2 O4 reacts with Ca2 SiO4 to form Ca12 Al14 O33, Ca2 Al2 SiO7 and CaAl2 Si2 O8 during the sintering process. The transition process CaAl2 O4 reacts with Ca2 SiO4 to form Ca12 Al14 O33 and Ca2 Al2 SiO7 could be restrained by controlling calcination temperature lower than 1350 °C or higher than 1500 °C with cooling in the furnace. Ca12 Al14 O33 and Ca2 Al2 SiO7 also could transform into CaAl2 O4 and Ca2 SiO4 again easily during the slow cooling process. The amounts of phases Ca12 Al14 O33 and Ca2 Al2 SiO7 generated at high temperature could stay stably at room temperature by cooling in the air immediately after the sintering process. The crystal transformation process of Ca2 SiO4 from γ to β starts at 1328 °C during the heating process. Furthermore, increasing calcination temperature higher than 1400 °C could restrain the crystal form transformation of Ca2 SiO4 from β to γ again during the cooling process. The formation of Ca2 Al2 SiO7, decreasing of CaAl2 O4 and γ-Ca2 SiO4 also could deteriorate the pulverization property and alumina leaching property of CaAl2 O4 -Ca2 SiO4 sample.